Dysmenorrhea Impact and Insights: A Statistical Analysis among Allied Health Professional Students in West Bengal, India - Goswami, Haimanti; Kumar, Debolina; Biswas, Swarnava (International Journal of Statistics in Medical Research, 2023)
Introduction: Dysmenorrhea is a prevalent gynecological disorder that is characterized by the presence of unpleasant menstrual cramps. This condition has been found to have significant medical, psychological, and social implications for individuals who experience it. Although commonly seen as an inherent characteristic of a properly functioning reproductive system, it can potentially operate as a diagnostic tool for underlying illnesses. Regrettably, dialogues pertaining to dysmenorrhea are sometimes prohibited, particularly among males, within diverse cultural contexts. Objective: The primary objective of this study is to evaluate the level of knowledge and attitudes among allied health professions students enrolled at various universities of West Bengal (WB), India with regard to dysmenorrhea. This study aims to examine the impact of cultural variables on the knowledge and communication surrounding dysmenorrhea, specifically within conservative Indian districts. Methods: The study sample consisted of 494 students enrolled in allied health professions faculties at different universities of WB. Data collection took place from September 2021 to February 2023. A meticulously designed survey was employed to gather data pertaining to the various sources of knowledge, levels of awareness, attitudes toward discussing dysmenorrhea, and willingness to engage in conversations about menstruation with prospective females. Data interpretation involved the utilization of statistical analysis techniques, such as descriptive statistics and correlation analysis. Results: In terms of demographic composition, the study consisted of 86% female participants and 14% male participants. The mean knowledge scores of females (14.41 ± 3.14) were found to be considerably higher compared to males (13.75 ± 4.56). The primary sources of information were the internet (58.3%), maternity figures (48.8%), and educational institutions (46.2%). An observed positive connection (r = 0.244) was found between age and knowledge levels. The participants exhibited a general hesitancy to openly engage in conversations on menstrual symptoms, however, they demonstrated a readiness to engage in discussions about menstruation with their prospective daughters. Conclusions: The present study brings attention to the gender discrepancies in knowledge levels pertaining to dysmenorrhea among allied health professions university students of WB. Additionally, it emphasizes the influence of cultural norms on knowledge acquisition and communication around this topic. The statement underscores the need for destigmatization initiatives, comprehensive teaching on menstruation health, and fostering open communication within academic institutions and the broader community. The aforementioned findings offer valuable insights that can inform future educational endeavors and healthcare procedures within this particular subject.